Morphological disparity across the K-Pg boundary in mollusk shells: A theoretical morphology approach - Gabriela Contreras-Figueroa; Austin J. W. Hendy; José L. Aragón (PLoS ONE, 2026)
Theoretical morphospace as a tool for understanding evolutionary changes in molluscan shell form is applied to analysis of biodiversity change across the Cretaceous-Paleogene extinction event. Although empirical morphospaces based on geometric morphometric descriptors are widely used, theoretical morphospaces offer better insights into the macroevolutionary constraints on morphospace occupation. The purpose of this work is to characterize the morphological disparity in mollusk shells during the Cretaceous and Paleogene, and specifically across the Cretaceous-Paleogene (K-Pg) boundary. Disparity measurements are derived from a recently proposed theoretical morphospace that is based on shell geometric parameters closely related to molluscan ecology and functional morphology. The case study focuses on representative families of the classes Bivalvia and Gastropoda, during the Late Cretaceous and early Paleogene of the Northeast Pacific coast, spanning from Washington to the Baja California Peninsula. The relationship between shell morphology and mode of life in mollusks and how geometric models can be used to understand shell morphology and disparity are discussed. Mapping bivalves and gastropods in morphospace across the K-Pg boundary reveals a marked loss of morphological disparity immediately after the extinction event. This was followed by a recovery during the Paleocene, particularly among infaunal and mobile taxa, where increased mobility and deposit-feeding strategies proved advantageous in low-nutrient environments. Applying the model to future research could contribute to the understanding of the paleoecological and ecomorphological factors that have influenced the diversity of these groups. We also note that the scarcity of disparity studies related to mollusks across the K-Pg boundary is striking and calls for more research in this area.